2015
DOI: 10.1142/s0192415x15500676
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cytotoxicity and the Anti-Adipogenic Effect of Green Tea Polyphenols with Epigallocatechin-3-Gallate in 3T3-L1 Preadipocytes

Abstract: Recent studies have demonstrated the effects of green tea polyphenols (GTP) and epigallocatechin-3-gallate (EGCG) on obesity. However, high doses of EGCG have also exhibited cytotoxicity. The aim of this study was to compare total GTP with purified EGCG on cytotoxicity, and to investigate the effects and the molecular mechanism of total GTP and EGCG on adipogenesis. Cytotoxicity was determined by cell viability assay. For the adipogenesis study, 3T3-L1 preadipocytes were incubated with three doses of GTP (1, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…In addition, a novel acylated flavonol tetraglycoside from Lu an GuaPian tea (a kind of green tea) remarkably inhibited the proliferation, differentiation, and lipid accumulation of 3T3-l1 cells [33]. Total green tea polyphenols might exhibit a greater inhibitory effect than purified EGCG on adipogenesis in 3T3-l1 cells, through decreasing adipogenic factors, including CCAAT element-binding protein α, peroxisome proliferator-activated receptor γ (PPAR γ), and sterol regulatory element-binding protein-1c (SREBP-1c) [155].…”
Section: Anti-obesity Effect In Vitromentioning
confidence: 99%
“…In addition, a novel acylated flavonol tetraglycoside from Lu an GuaPian tea (a kind of green tea) remarkably inhibited the proliferation, differentiation, and lipid accumulation of 3T3-l1 cells [33]. Total green tea polyphenols might exhibit a greater inhibitory effect than purified EGCG on adipogenesis in 3T3-l1 cells, through decreasing adipogenic factors, including CCAAT element-binding protein α, peroxisome proliferator-activated receptor γ (PPAR γ), and sterol regulatory element-binding protein-1c (SREBP-1c) [155].…”
Section: Anti-obesity Effect In Vitromentioning
confidence: 99%
“…The mouse adipocyte 3T3-L1 cell line has been extensively used to study the in vitro effect of tea extracts and its isolated compounds [71][72][73]. In obesity in vivo studies, C57BL/6J mice are the most widely animal model since they are susceptible to high fat diet-induced obesity [74,75].…”
Section: Camellia Sinensis and Obesitymentioning
confidence: 99%
“…Moreover, the mitogen activated protein kinases (MAPKs) signaling pathways (extracellular signal regulated kinases (ERKs), Jun amino terminal kinases (JNKs), and stress activated protein kinases (p38/SAPKs)) are involved in adipocyte differentiation and in adipogenesis regulation [79]. Green tea polyphenols, gallocatechin gallate, and epigallocatechin-3-gallate decreased MAPK pathway activation as evidenced in downregulation of adipogenic factor expression (CCAAT element binding protein α (C/EBPα), peroxisome proliferator-activated receptor gamma (PPARγ), and sterol regulatory element-binding protein-1c (SREBP-1c)) in a differentiated mouse adipocyte 3T3-L1 cell line [72,73]. Furthermore, the compound gallocatechin gallate has also demonstrated inhibition of inflammation through NF-κB signaling; adipose tissue inflammation is involved in several pathologies associated with obesity such as diabetes mellitus type 2 [73].…”
Section: Camellia Sinensis and Obesitymentioning
confidence: 99%
“…This adipogenic medium was refreshed every 2 days. The numbers of mature adipocytes was determined by visual inspection of the lipid droplet formation under light microscopy (Olympus, BX51 microscope, Tokyo, Japan) followed by Oil Red O staining (Sigma-Aldrich, St Louis, MO, USA) and triglycerides measurement described previously [11] on day 7, 14, 21 and 28 after induction treatment. Triglyceride contents were increased more than 10 times on day 21 of adipogenic induction.…”
Section: Hadscs Differentiation and Treatmentmentioning
confidence: 99%
“…Our previous studies showed that GTP exert anti-adipogenic effects on preadipocyte proliferation in 3T3-L1 adipocytes [11] and ameliorate metabolic abnormalities and insulin resistance in obese Zucker fatty rats [12]. In the present study we evaluated whether GTP is capable of modulating the differentiation of human adipose tissue-derived stem cells (hADSCs) shifting towards osteogenic lineage and suppressing adipogenesis during early stage of differentiation.…”
Section: Introductionmentioning
confidence: 98%